Meningioma surgical outcomes and complications in patients aged 75 years and older. (June 2021) - Ekaireb, Rachel I.; Edwards, Caleb S.; Ali, Muhammad S.; Nguyen, Minh P.; Daggubati, Vikas; Aghi, Manish K.; Theodosopoulos, Philip V.; McDermott, Michael W.; Magill, Stephen T.
Highlights: Retrospective review of 103 patients with meningioma that underwent surgical resection and were 75 years and older. Median postoperative actuarial survival was 10.5 years. Complications occurred in 31% of patients, and 13% of patients had multiple complications. Cardiovascular comorbidities and male gender were significant preoperative risk factors associated with complications. Abstract: Objective: Meningioma incidence increases with age, yet limited data exist on how comorbidities impact complication rates in elderly patients undergoing meningioma resection. The objective of this study was to report surgical outcomes and identify risk factors for perioperative complications. Methods: We performed a retrospective study of patients 75 years and older undergoing meningioma resection. Outcomes included survival and complications. Major complications were those requiring surgical intervention or causing permanent neurological deficit. Recursive partitioning, Kaplan-Meier survival, univariate and multi-variate (MVA) analyses were performed. Results: From 1996 to 2014, 103 patients with a median age of 79 years (IQR 77–83 years) underwent cranial meningioma resection. Median follow-up was 5.8 years (IQR 1.7–8.7 years). Median actuarial survival was 10.5 years. Complications occurred in 32 patients (31.1%), and 13 patients (12.6%) had multiple complications. Major complications occurred in 16 patients (15.5%). Increasing age was not a significant predictor of any (p = 0.6408) or major complication (p = 0.8081). On univariate analysis, male sex, Charlson Comorbidity Index greater than 8, and cardiovascular comorbidities were significantly associated with major complications. On MVA only cardiovascular comorbidities (OR 3.94, 95% CI 1.05–14.76, p = 0.0238) were significantly associated with any complication. All patients with major complications had cardiovascular comorbidities, and on MVA male gender (OR 3.78, 95%CI 1.20–11.93, p = 0.0212) was associated with major complications. Conclusions: Cardiovascular comorbidities and male gender are significant risk factors for complications after meningioma resection in patients aged 75 years and older. While there is morbidity associated with meningioma resection in this cohort, there is also excellent long-term survival.